Platelet function changes in patients undergoing endovascular aortic aneurysm repair: Review of the literature - Burban, Anna; Idzik, Aleksandra; Gelo, Agata; Filipiak, Krzysztof J.; Jakimowicz, Tomasz; Jama, Katarzyna; Grabowski, Marcin; Gasecka, Aleksandra; Siniarski, Aleksander (Frontiers in Cardiovascular Medicine, 2022)
Patients with abdominal aortic aneurysm (AAA) have a higher risk of cardiovascular (CV) events, which seems to be associated with disturbed platelet (PLT) function. Endovascular aneurysm repair (EVAR) is an emerging, less-invasive treatment alternative to surgical AAA repair. Both platelet function abnormalities in patients with AAA and the effect of EVAR on platelet function are poorly understood. In this review, we aim to fill the gap regarding the effect of EVAR on PLT function in AAA patients by discussing PLT function disturbances in patients with AAA, PLT function changes after EVAR, evidence from clinical studies regarding PLT function before and after EVAR, and antiplatelet or and antithrombotic treatment in patients undergoing EVAR. The goal of our review is to summarize the contemporary knowledge and initiate further studies to better understand PLT function changes in patients undergoing EVAR, optimize the pharmacotherapy before and after EVAR and further improve outcomes in this group of patients.